Pseudo-understanding. An Agreement between Media and its Customers - Maya Franco, Claudia (2017)
A relationship is established between the media and its clients that is not explained by appealing to the law of causes and effects. It could be said rather that it is a dialogic relationship, deeply rooted in the logic of supply and demand. In this text, from the relationship proposed by Heidegger (and that is also dialogical) between understanding and pseudo-understanding, speech and gossip (and referring to the notion of cultural industry), it is suggested that the often fallacious character of the exercise of information is determined not only by the means and interests they hold, but by those to whom we have called their clients.